(untitled) (Bioagro, 2026)
Mango is one of the most important agricultural export products in northern Peru. Therefore, it is necessary to think about methods for producing high-quality seedlings to ensure good crop development. The objective of this study was to investigate the effect of hydrogen peroxide on the emergence and initial growth of mango seedlings. Four concentrations (C) of the product (0, 10, 30, and 50 % H₂O₂) and two imbibition times (T) (6 and 12 h) were evaluated in a factorial arrangement for a total of eight treatments in mango ‘Criollo de Chulucanas’ (apomixis: polyembryony). For the evaluation, the most vigorous shoots and main root were selected. The percentage of emergence (PE), main root length (RL), plant height (PH), main root diameter (RD), stem diameter (SD), number of leaves (NL), shoot and root fresh weight (SFW and RFW), and total soluble solids of root (TSSr) were determined. The results showed a positive effect of treatment C2*T1 on PE, RD, RL, SFW and RFW, and of C4*T1 and C4*T2 on TSSr. Treatment C3*T2 increased SD. These same relationships were observed in the principal component analysis (PCA) and cluster analysis. Correlation analysis showed that PE was positively correlated with RD and RFW, as was RD with SFW, and RL with RFW. The variable TSSr showed a negative correlation with SFW. It is concluded that seed treatment with hydrogen peroxide is a safe alternative to stimulate seedling emergence and development in mango.